2006
DOI: 10.1002/gps.1670
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to potentially harmful behaviors towards disabled older people by family caregivers in Japan

Abstract: In the present study, PHB towards the older people by family caregivers was associated with patients' behavioral disturbances and patient-caregiver kinship, i.e. an adult child as a caregiver. These findings should be taken into account when planning strategies to prevent PHB by family members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
4
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 25 publications
5
47
4
2
Order By: Relevance
“…Oh ve arkadaşları tarafından yapılan çalışmada, istismarın 2/3'sinin daha fazlasını (%75-%80) yaşlıların oğulla-rı ya da kız çocukları tarafından (10) , Sasaki ve arkadaşları (39) %33.7'sinin büyük erkek çocukları, %19,3'ünün kız çocukları tarafından, Muehlbauer ve arkadaşları (40) %90'ının aile üyeleri tarafından, İlhan %30.7'sinin gelini, %23.1'ininin oğlu, %15.4'ünün ise kızı tarafından (41) , Boldy ve arkadaşları (42) %22'sinin kız çocukları, %21'nin erkek çocukları, %18'inin eşleri, %17'sinin diğer akrabaları ve %5'ini ise torunları tarafından yapıldığını belirlemişlerdir. Bulgular yaşlıların daha çok erkek çocukları tarafın-dan istismar edildiğini düşündürmektedir.…”
unclassified
“…Oh ve arkadaşları tarafından yapılan çalışmada, istismarın 2/3'sinin daha fazlasını (%75-%80) yaşlıların oğulla-rı ya da kız çocukları tarafından (10) , Sasaki ve arkadaşları (39) %33.7'sinin büyük erkek çocukları, %19,3'ünün kız çocukları tarafından, Muehlbauer ve arkadaşları (40) %90'ının aile üyeleri tarafından, İlhan %30.7'sinin gelini, %23.1'ininin oğlu, %15.4'ünün ise kızı tarafından (41) , Boldy ve arkadaşları (42) %22'sinin kız çocukları, %21'nin erkek çocukları, %18'inin eşleri, %17'sinin diğer akrabaları ve %5'ini ise torunları tarafından yapıldığını belirlemişlerdir. Bulgular yaşlıların daha çok erkek çocukları tarafın-dan istismar edildiğini düşündürmektedir.…”
unclassified
“…In our previous study (Sasaki et al, 2007), behavioral disturbances of older people and an adult child as the caregiver have been found to be associated with PHB towards disabled older people. Thus, these two factors should be taken into account in order to prevent PHB from family caregivers; thereby delaying institutionalization among community-residing disabled older people.…”
Section: Discussionmentioning
confidence: 97%
“…The authors recently reported factors related to PHB towards disabled older people in a crosssectional study (Sasaki et al, 2007). The present study is a two-year follow-up study.…”
Section: Introductionmentioning
confidence: 94%
“…Research has determined risk factors for elder abuse for both victims and caregivers. On the part of the victims, suggested factors include greater care needs [1,2], cognitive decline [1,3], behavioral symptoms [4][5][6], poor social support [4,7,8] and a long-term relationship with the caregiver [4]. Factors for the caregiver include alcohol abuse [9], mental health or behavioral problems [2], low income [10], and financial dependency on the victim [4].…”
Section: Introductionmentioning
confidence: 98%